2011
DOI: 10.1007/s10681-011-0572-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of year and genetic factors on chilling injury susceptibility in peach (Prunus persica (L.) Batsch)

Abstract: Chilling injury (CI) is a major physiological problem limiting consumption and export of peach and nectarine (Prunus persica (L.) Batsch). To clarify the genetic basis for chilling injury, inheritance of the major CI symptoms mealiness, flesh browning, flesh bleeding, and flesh leatheriness were examined over three years in two related peach progenies. In addition, genetic relationships among traits and the year-to-year variation in trait performance in these progenies were tracked. Both populations also segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(53 reference statements)
2
10
0
Order By: Relevance
“…These authors reported that mealiness was almost non‐existent in the CNMF progeny, while bleeding incidence was higher in the CNMF progeny after 2–3 weeks of cold storage . Similarly, Martínez‐García et al reported that flesh bleeding occurs primarily in non‐melting‐flesh fruit, particularly when the fruit is white‐fleshed. Interestingly, the results of this work showed at least 17 genotypes (20, 22, 33, 44, 58, 68, 70, 72, 76, 80, 81, 96, 106, 118, 120, 124 and 129) with low susceptibility to CI symptoms and with several good organoleptic traits (values for fruit weight, vitamin C, RAC, total phenolics, flavonoids or sugars over the average).…”
Section: Resultssupporting
confidence: 84%
“…These authors reported that mealiness was almost non‐existent in the CNMF progeny, while bleeding incidence was higher in the CNMF progeny after 2–3 weeks of cold storage . Similarly, Martínez‐García et al reported that flesh bleeding occurs primarily in non‐melting‐flesh fruit, particularly when the fruit is white‐fleshed. Interestingly, the results of this work showed at least 17 genotypes (20, 22, 33, 44, 58, 68, 70, 72, 76, 80, 81, 96, 106, 118, 120, 124 and 129) with low susceptibility to CI symptoms and with several good organoleptic traits (values for fruit weight, vitamin C, RAC, total phenolics, flavonoids or sugars over the average).…”
Section: Resultssupporting
confidence: 84%
“…In peaches, this mealy texture is most often caused by internal tissue breakdown due to chilling injury (CI) (Lurie and Crisosto, 2005), and can significantly lower the consumer acceptability of fruit with above-average peach flavor metrics (Crisosto, 2002). In peach, mealy texture is partly determined by texture type (melting) and genetic tests have been developed to screen for susceptible varieties in breeding programs (Martínez-García et al, 2012).…”
Section: Meatymentioning
confidence: 99%
“…Transcriptomic studies after cold storage using single genotypes (González-Agüero et al, 2008 ; Ogundiwin et al, 2008 ; Vizoso et al, 2009 ; Pavez et al, 2013 ) or contrasting genotypes with differential susceptibility to cold (Falara et al, 2011 ; Dagar et al, 2013 ; Pons et al, 2014 , 2015 ) have been powerful approaches in order to dissect the molecular mechanisms involved in peach cold tolerance. In addition, proteomic studies have also identified key proteins involved in the protection to cold or in the development of CI (Lara et al, 2009 ; Dagar et al, 2010 ; Nilo et al, 2010 ; Zhang et al, 2010 ; Almeida et al, 2016 ); while genomic studies have allowed the mapping of a number of quantitative trait loci (QTL) for CI in the peach genome (Ogundiwin et al, 2009 ; Cantín et al, 2010 ; Dhanapal et al, 2012 ; Martinez-Garcia et al, 2012 ; Nuñez-Lillo et al, 2015 ). These studies have indicated that CI is a multigenic quantitative trait, and thus, genetic engineering of CI tolerance is a very difficult challenge.…”
Section: Introductionmentioning
confidence: 99%